Integrasi Nilai Qur’ani dalam Penguatan Karakter Pelajar di Era Digital 5.0 - Jabar, Abdul; Subagyo, Ahmad (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
The rapid digital transformation in the Society 5.0 era presents both challenges and opportunities in the field of education, particularly in shaping students' character. This paper aims to offer integrative strategies for embedding Qur’anic values into the character education system as a solution to the moral degradation and identity crisis emerging in the digital age. Using literature review and content analysis methods on verses of the Qur’an, it is found that the Qur’an provides a strong foundation for character development, promoting honesty, responsibility, compassion, and discipline as essential traits for students to navigate the complexities of modern life. By internalizing these values, students are expected to develop critical thinking, ethical awareness, and social responsibility when engaging with technology and information. This article suggests that Islamic education curricula should position Qur’anic values as the core of character reinforcement, not merely as an additional element of spiritual practice. Educators, parents, and communities are encouraged to collaborate in creating learning environments that reflect and nurture these values consistently. Through an integrated approach, this paper hopes to contribute to strengthening the character of students so they are prepared to face global challenges without losing their identity and moral compass in the digital era